2015
DOI: 10.1001/jamaophthalmol.2014.4755
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies in Primary Vitreoretinal Lymphoma

Abstract: IMPORTANCE The best treatment option for primary vitreoretinal lymphoma (PVRL) without signs of central nervous system lymphoma (CNSL) involvement determined on magnetic resonance imaging or in cerebrospinal fluid is unknown. OBJECTIVE To evaluate the outcomes of treatment regimens used for PVRL in the prevention of subsequent CNSL. DESIGN, SETTING, AND PARTICIPANTS A retrospective cohort study was conducted at 17 referral ophthalmologic centers in Europe. We reviewed clinical, laboratory, and imaging data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 30 publications
3
121
4
1
Order By: Relevance
“…Most cases are classified as diffuse large B-cell lymphomas (DLBCLs) and represent either primary VRL or secondary ocular involvement by primary central nervous system lymphoma (PCNSL). [1][2][3][4][5] VRLs are highly aggressive tumors that need to be distinguished from the second most common intraocular lymphoma, low-grade choroidal extranodal marginal zone B-cell lymphomas, which are not associated with central nervous system (CNS) disease but which do occasionally extend extraocularly. 2 VRL is usually diagnosed by cytologic, immunocytochemical, and molecular examination of vitreous body aspirates.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases are classified as diffuse large B-cell lymphomas (DLBCLs) and represent either primary VRL or secondary ocular involvement by primary central nervous system lymphoma (PCNSL). [1][2][3][4][5] VRLs are highly aggressive tumors that need to be distinguished from the second most common intraocular lymphoma, low-grade choroidal extranodal marginal zone B-cell lymphomas, which are not associated with central nervous system (CNS) disease but which do occasionally extend extraocularly. 2 VRL is usually diagnosed by cytologic, immunocytochemical, and molecular examination of vitreous body aspirates.…”
Section: Introductionmentioning
confidence: 99%
“…A multicentre study by Riemens et al 24 stated that incidence of CNS relapse was similar in patients treated with only local ocular therapy as in patients with systemic treatment (various combinations of systemic and intrathecal chemotherapy, whole-brain radiotherapy and peripheral blood stem cell transplantation). Riemens et al 24 emphasised the severe adverse effects accompanying systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study showed no evidence that systemic therapy prolongs survival in patients presenting with vitreoretinal lymphoma [6]; however, this situation may be improving thanks to therapeutic advances. Whether the systemic therapy has prevented overt CNS disease in our patient is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In most centers, vitreoretinal lymphoma is treated focally, with ocular radiotherapy or intravitreal chemotherapy [3-5]. About one-third of patients develop CNS disease within 5 years [6]. At the University of California San Francisco (UCSF), we treat vitreoretinal lymphoma with systemic chemotherapy, usually in combination with rituximab and lenalidomide, a second-generation immunomodulatory agent [7].…”
Section: Introductionmentioning
confidence: 99%